Recent Progress in Near Infrared Light Triggered Photodynamic Therapy - Deng, Kerong; Li, Chunxia; Huang, Shanshan; Xing, Bengang; Jin, Dayong; Zeng, Qingguang; Hou, Zhiyao; Lin, Jun (Small (Weinheim an der Bergstrasse, Germany), 2017)
Nowadays, photodynamic therapy (PDT) is under the research spotlight as an appealing modality for various malignant tumors. Compared with conventional PDT treatment activated by ultraviolet or visible light, near infrared (NIR) light‐triggered PDT possessing deeper penetration to lesion area and lower photodamage to normal tissue holds great potential for in vivo deep‐seated tumor. In this review, recent research progress related to the exploration of NIR light responsive PDT nanosystems is summarized. To address current obstacles of PDT treatment and facilitate the effective utilization, several innovative strategies are developed and introduced into PDT nanosystems, including the conjugation with targeted moieties, O2 self‐sufficient PDT, dual photosensitizers (PSs)‐loaded PDT nanoplatform, and PDT‐involved synergistic therapy. Finally, the potential challenges as well as the prospective for further development are also discussed. Near infrared (NIR) light triggered photodynamic therapy (PDT) has gained much attention as a promising treatment for malignant tumors. This Review presents an overview of recent progress on the development of NIR light‐activated photosensitizers (PSs), and the design of advanced NIR light triggered PDT nanosystems including tumor‐targeted PDT, O2 self‐sufficient PDT, dual PSs‐loaded PDT, and PDT involved synergistic therapy.